WORK ON VOCAL WORKS IN PROCESS STUDENT EDUCATION (Pedagogy of Higher and Secondary Education, 2002)
A future teacher must became highly skilled specialist with initiative. He must hold all methods of work in selection of vocal repertoire and composition's interpretation.In the process of education, a teacher must upbring a student by positive examples, form his personality.